Pubococcygeal Sling versus Refixation of the Pubocervical Fascia in Vesicovaginal Fistula Repair: A Retrospective Review - Rachel Pope; Prakash Ganesh; Jeffrey Wilkinson (Hindawi Limited, 2018)
Urethral incontinence is an issue for approximately 10-15% of women with an obstetric fistula. Various surgical interventions to prevent this exist, including the pubococcygeal sling and refixation of the pubocervical fascia. Neither has been evaluated in comparison to one another. Therefore, this retrospective evaluation for superiority was performed. The primary outcome was urinary stress incontinence, and secondary outcomes were operative factors. There were 185 PC slings, but 12 were excluded because of urethral plications. There were 50 RPCF procedures, but 3 were excluded because of urethral plications. Finally, there were 32 cases with both PC sling and RPCF procedures. All groups demonstrated a higher than expected fistula repair rate with negative dye tests in 84% of the PC sling group, 89.9% in the RPCF group, and 93.8% in the RPCF and PC groups. There were no statistically significant differences found in continence status between the three groups. Of those who underwent PC slings, 49% were found to have residual stress incontinence. Of those who underwent RPCF, 47.8% had stress incontinence. Of those with both techniques, 43.8% had residual stress incontinence. Pad weight was not significantly different between the groups. As there is no statistically significant difference, we cannot recommend one procedure over the other as an anti-incontinence procedure. The use of both simultaneously is worth investigating.